(untitled) (Agroindustrial Science, 2023)
The production of coal from biomass emerges as a sustainable alternative, both to take advantage of waste and to protect the environment. This research aims to take advantage of aguaje seeds to make ecochar. First, the seeds (from Pucallpa and Yurimaguas) were characterized proximally. They were then characterized morphologically (length, diameter, and weight), both fresh and dehydrated. In the second part, the carbonization was carried out, using a Completely Random Design with factorial arrangement. The first factor was the state of the seed (fresh and dehydrated), and the second was the carbonization method (open and boxed), the response variable being yield. In the third stage, briquettes were made, mainly evaluating the calorific value. The results showed that solar dehydration similarly reduced the weight of the seeds. The state of the seed and the carbonization method have a significant effect on the yield, being the best treatment with dry seed and open carbonization (yield 25.77%). This treatment also obtained the highest calorific value (6716.93 cal/g) in the final briquettes, higher by almost 25% than that of traditional briquettes.